Conceptualisation and Determination of the Concept of Creating Shared Value: The Results of a Delphi Study - Krawiec, Wioletta; Sibińska, Anna; Grzegorczyk, Wojciech (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The purpose of the article is to present the genesis of the concept of Creating Shared Value (CSV), re-conceptualise it, and point out the main dimensions of value creation. In addition, the article describes the existing interdependencies between the various dimensions and the distinct approaches to defining these dimensions.Research Design & Methods: The article presents the results obtained from an expert survey conducted using the Delphi method. The survey allowed us to obtain experts’ opinions on approaches to defining the creation of shared value and its dimensions.Findings: The results obtained suggest a different approach to understanding and defining the concept of CSV and the dimensions of value creation. In the study experts pointed to the connection of the CSV concept with other management theories and concepts in corporate social responsibility and sustainability. They emphasised the role of creating shared value to different stakeholder groups in the complex internal and external business environment. The difficulty of linking company strategy, business models, and activities with social, environmental, or economic goals was pointed out.Implications / Recommendations: The article presents the results obtained from the first part of a study aimed at constructing a tool to measure the creation of shared value. They are the starting point for both the development of the dimensions of the construct and the factors which can be measured to evaluate the creation of social, economic and environmental value in each dimension.Contribution: The article contributes to the understanding of the concept of CSV as a management theory in the context of enhancing the competitive position of organisations and provides a methodological basis for developing a CSV measurement tool.